Occurrence of Grapevine Pinot gris virus in Friuli Venezia Giulia (Italy): field monitoring and virus quantification by real‐time RT‐PCR. (7th April 2015) - Bianchi, G. L.; De Amicis, F.; De Sabbata, L.; Di Bernardo, N.; Governatori, G.; Nonino, F.; Prete, G.; Marrazzo, T.; Versolatto, S.; Frausin, C.
Abstract : Since 2003 the presence of a new syndrome characterized by symptoms of stunting, chlorotic mottling, leaf deformation, reduced yields and quality has been reported in some white berry varieties of Vitis vinifera in Trentino‐Alto Adige and Friuli Venezia Giulia vineyards. The identification of a new virus, provisionally called Grapevine Pinot gris virus (GPGV), in a cv. Pinot gris vine suggested an association between this new syndrome and the virus presence (Giampetruzzi et al ., 2012), however the contemporary presence of GPGV in both symptomatic and asymptomatic plants has still to be explained. In this work, a large‐scale monitoring over a 3‐year period (2012–14) of Friuli Venezia Giulia vineyards and nurseries has shown a widespread presence of GPGV in symptomatic plants and also in asymptomatic vines, even if at a slightly lower percentage. Quantitative analyses of the virus titer revealed a great variability in the viral content of both symptomatic and asymptomatic plants but the mean GPGV quantity in symptomatic vines was significantly higher than in asymptomatic plants.